Monocytes in HIV and SIV Infection and Aging: Implications for Inflamm-Aging and Accelerated Aging - Zoey K. Wallis; Kenneth C. Williams (Viruses, 2022)
Before the antiretroviral therapy (ART) era, people living with HIV (PLWH) experienced complications due to AIDS more so than aging. With ART and the extended lifespan of PLWH, HIV comorbidities also include aging—most likely due to accelerated aging—as well as a cardiovascular, neurocognitive disorders, lung and kidney disease, and malignancies. The broad evidence suggests that HIV with ART is associated with accentuated aging, and that the age-related comorbidities occur earlier, due in part to chronic immune activation, co-infections, and possibly the effects of ART alone. Normally the immune system undergoes alterations of lymphocyte and monocyte populations with aging, that include diminished naïve T- and B-lymphocyte numbers, a reliance on memory lymphocytes, and a skewed production of myeloid cells leading to age-related inflammation, termed “inflamm-aging”. Specifically, absolute numbers and relative proportions of monocytes and monocyte subpopulations are skewed with age along with myeloid mitochondrial dysfunction, resulting in increased accumulation of reactive oxygen species (ROS). Additionally, an increase in biomarkers of myeloid activation (IL-6, sCD14, and sCD163) occurs with chronic HIV infection and with age, and may contribute to immunosenescence. Chronic HIV infection accelerates aging; meanwhile, ART treatment may slow age-related acceleration, but is not sufficient to stop aging or age-related comorbidities. Overall, a better understanding of the mechanisms behind accentuated aging with HIV and the effects of myeloid activation and turnover is needed for future therapies.